Sosialisasi Penggunaan Sistem Statistik pada Metode Latihan Olahraga Petanque - Nur Salsabila Rhesa P. P.; Nurhasan Nurhasan; Suryanto Agung Prabowo (Jurnal Informasi Pengabdian Masyarakat, 2026)
The outreach program on the use of statistical systems in petanque training methods aims to improve the effectiveness of training and athletes’ performance through the use of data. The dissemination process consists of five main steps: (1) an introduction to the importance of statistical data for analyzing performance, strengths, weaknesses, and opponents’ strategies; (2) a technical demonstration of how to use the system to record and interpret training and match data; (3) a question-and-answer session to address obstacles and misunderstandings; (4) a hands-on workshop to provide direct experience in collecting and analyzing data in real time; and (5) an evaluation and feedback session following the implementation period to refine the system. Additionally, this training emphasizes participant safety and well-being, including injury prevention and adherence to safety protocols through the role of trained referees. The overall objective of these activities is to create a safe, measurable, and data-driven training and competition environment.